Intorno alla circolazione del mito su Eracle in età imperiale - Cutuli, Silvia (Lexis, 2023)
The fifth Imago of Philostratus Minor, which portrays baby Heracles’ struggle against the snakes sent from Hera, appears to be inspired by two Pindaric works (Nem. 1 and *Pae. 20). This paper explores the possibility that some linguistic features of Philostratus’ ekphrasis can be borrowed (presumably by secondary source) from Panyassis’ lost Herakleia. By going against the communis opinio, it is suggested that this archaic exametric poem may have survived through Imperial Age, until the 2nd century AD, alongside other mythographic and poetic works about the Heracles’ saga.